The prevalence and genotype of 21-hydroxylase deficiency in the Croatian Romani population - Dumic, Katja K.; Grubic, Zorana; Kusec, Vesna; Braovac, Duje; Gotovac, Kristina; Vinkovic, Maja; Vucinic, Maja; Dumic, Miroslav (Frontiers in Endocrinology, 2023)
Objective. Congenital adrenal hyperplasia (CAH) owing to 21-hydroxylase deficiency (21-OHD) is a rare autosomal recessive disorder caused by mutations in the CYP21A2 gene. After a high prevalence of classic 21-OHD CAH in Romani population was reported in the Republic of North Macedonia we decided to estimate prevalence of 21-OHD in Croatia, and if high, assess the possible causes and estimate frequency of particular CYP21A2 mutations. Design. Cross-sectional study. Methods. Data from Croatian 21-OHD genetic database was reviewed, and only Romani patients were included in the study. CYP21A2 genotyping was performed by allele-specific PCR, MLPA and Sanger sequencing. Results. According to a survey conducted in 2017, Croatia had 22 500 Romani people and six of them had salt-wasting (SW) form of 21-OHD. All were homozygous for c.IVS2-13A/C-G mutation in Intron 2 and descended from consanguineous families belonging to different Romani tribes. The calculated prevalence of 21-OHD in Croatian Romani is 1:3 750, while in the Croatian general population it is 1:18 000. Three of the six Romani patients originated from two neighboring villages in North-western Croatia (Slavonia County), as well as the seventh patient who is of mixed Romani/Croatian descent and heterozygous for c.IVS2-13A/C-G mutation (not included in prevalence calculation). Conclusion. High prevalence of SW 21-OHD in Croatian Romani population caused by homozygous cIVS2-13A/C-G mutation was found. Beside isolation and consanguinity, a possible reason could be heterozygous advantage of CYP21A2 gene mutation and bottle neck effect as a result of Romani Holocaust in World War II.